The bumpy face of che guevara: An interesting case - Kingshuk Chatterjee; Anupam Roy; Romana Ghosh; Jayanta Kumar Barua; Saswati Halder; Gautam Banerjee (Wolters Kluwer Medknow Publications, 2017)
Placement of decorative tattoo on the skin may lead to various immunological, infective, and coincidental complications. Inoculation of human papillomavirus leading to development of verruca is an uncommon complication of tattoos. The present report highlights the development of verruca vulgaris, developing after 2 years of tattooing in a young male.